PENGARUH PERCEIVED QUALITY DAN BRAND REPUTATION TERHADAP REPURCHASE INTENTION PT. MAKMUR BINTANG PLASTINDO - Agustina; Errie Margery; Seri (Jurnal Mahkota Bisnis (Makbis), 2025)
This research was conducted on consumers at PT. Makmur Bintang Plastindo. The purpose of this research is to determine and analyze the influence of Perceived Quality and Brand Reputation on Repurchase Intention. The population and sample in this study amounted to 55 people. The sampling technique used was saturated. The data collection technique is by distributing questionnaires and interviews. Data analysis uses multiple linear regression analysis. The conclusion in the research is that simultaneously Perceived Quality and Brand Reputation have a positive and significant effect on PT's Repurchase Intention. Makmur Bintang Plastindo. Partially, Perceived Quality influences on PT's Repurchase Intention. Makmur Bintang Plastindo. Partially, Brand Reputation influences PT's Repurchase Intention. Makmur Bintang Plastindo. The magnitude of the coefficient of determination can be seen from the Adjusted R Square value of 0.324. This means that the magnitude of the influence of Perceived Quality and Brand Reputation on Repurchase Intention is 0.324 or 32.4% and the remaining 67.6% is influenced by other factors outside the research model such as Promotions, Discounts, Personal Selling, etc.